Devonian plant remains of the Donets basin from the Geological Museum collection of Taras Shevchenko Kyiv National University - BOIARINA, N.; USTYNOVSKA, M.; NESTEROVSKYI, V.; VAKULENKO, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Preview results of the study of a Devonian plant remains collection from the Donets basin collected by M.I. Ustinovskaya and stored in the Geological Museum of the Kiev National University of T. Shevchenko are given. Fossil macroflora is represented by psilophytes, lycophytes, sphenophylls, ferns, progymnosperms and gymnosperms. In the Donets basin, representatives of family Barrandeinaceae are determinated for the first time and Barrandeina sp. is described.